Modernity and existence from a semiotic angle. The Voyeurism of the City in Struktura kryształu (1969), a film directed by Krzysztof Zanussi - Kaźmierczak, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Krzysztof Zanussi’s Struktura kryształu [The Structure of Crystals] is a film not only semiotically but also mythologically rich, in the context of myths as understood and proposed by Roland Barthes. The article explores the binary nature of the film’s symbolic layer, built upon the two distinct life realities: the metropolitan vs the rural, the prestige of an academic career vs the simplicity of a family life that the main characters chose for themselves.